2006
DOI: 10.1085/jgp.200609490
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Features of the S- and M-cone Photoreceptors of Wild-type Mice from Single-cell Recordings

Abstract: Cone cells constitute only 3% of the photoreceptors of the wild-type (WT) mouse. While mouse rods have been thoroughly investigated with suction pipette recordings of their outer segment membrane currents, to date no recordings from WT cones have been published, likely because of the rarity of cones and the fragility of their outer segments. Recently, we characterized the photoreceptors of Nrl −/− mice, using suction pipette recordings from their “inner segments” (perinuclear region), and found them to be cone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
367
3
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(413 citation statements)
references
References 59 publications
(113 reference statements)
38
367
3
1
Order By: Relevance
“…3). M-cone photoreceptor currents, recorded from mouse outer segments are observed to peak around 70 ms after a weak flash and to recover to baseline in around 200 ms (Nikonov et al, 2006). Times to peak for stronger flashes such as we used would be earlier.…”
Section: Isolation and Time Course Of Cone Photoreceptor-driven Respomentioning
confidence: 91%
See 1 more Smart Citation
“…3). M-cone photoreceptor currents, recorded from mouse outer segments are observed to peak around 70 ms after a weak flash and to recover to baseline in around 200 ms (Nikonov et al, 2006). Times to peak for stronger flashes such as we used would be earlier.…”
Section: Isolation and Time Course Of Cone Photoreceptor-driven Respomentioning
confidence: 91%
“…This duration is very prolonged compared to results from suction electrode recordings from mouse M-cones. In suction electrode recordings, outer segment currents were reduced only for about 200 ms for weak stimuli, with a peak reduction around 70 ms after a brief flash (Nikonov et al, 2006). In the present study, in order to isolate the cone photoreceptor contribution to the ERG, the paired flash approach (Pepperberg et al, 1997) was used to derive the photocurrent.…”
Section: Photoreceptor Contributions To the Mouse Light-adapted Ergmentioning
confidence: 97%
“…Cone function in Nrl knockout mice is preserved as late as 31 weeks ). Single-cell electrophysiology showed responses driven by both S-and M-opsin in all cells tested from Nrl knockout mice , as seen for the wild-type cones that co-express both opsins [ (Applebury et al, 2000;Nikonov et al, 2006); see cone subtypes and gradients section below]. Although the dorsal/ventral M/S-cone gradient is preserved in Nrl −/− mice, more S-opsin sensitivity is seen in Nrl −/− cones than in wild-type cones from comparable dorsal/ventral levels of the retina (Nikonov et al, 2006).…”
Section: Animal Studiesmentioning
confidence: 92%
“…Single-cell electrophysiology showed responses driven by both S-and M-opsin in all cells tested from Nrl knockout mice , as seen for the wild-type cones that co-express both opsins [ (Applebury et al, 2000;Nikonov et al, 2006); see cone subtypes and gradients section below]. Although the dorsal/ventral M/S-cone gradient is preserved in Nrl −/− mice, more S-opsin sensitivity is seen in Nrl −/− cones than in wild-type cones from comparable dorsal/ventral levels of the retina (Nikonov et al, 2006). Consistent with the above electrophysiological measures, the ultrastructural analysis showed that the Nrl −/− retina has much shorter cone-like outer segments with disrupted morphology and cone-like nuclei with decondensed chromatin Daniele et al, 2005).…”
Section: Animal Studiesmentioning
confidence: 92%
“…For these two wavelengths, the intensities were equivalent to photo-isomerization rates (in s Ϫ1 per cone) of 2730 -14,800 for blue in S-cones and 1670 -9000 for green in M-cones (assuming exclusive M-opsin expression). This was calculated using the relative sensitivities of the mouse cone opsins at the stimulus wavelengths via an opsin-template (Stockman and Sharpe, 2000) fitted to the peak sensitivities (360 and 511 nm) (Jacobs et al, 1991) and assuming the light collection area of a cone a c ϭ 0.2 m 2 (Nikonov et al, 2006). We lightadapted the slices during the experiment to the low photopic range by presenting a background intensity of Ϸ10 5 photons ⅐ s Ϫ1 ⅐ m…”
Section: Methodsmentioning
confidence: 99%